EP 138. Impact of recurrent mild traumatic brain injury on GABA concentration and GABAB receptor activity. Issue 9 (September 2016) - Wilke, S.; List, J.; Mekle, R.; Lindenberg, R.; Bukowski, M.; Ott, S.; Schubert, F.; Flöel, A.
Abstract : Introduction: As patients with mild traumatic brain injury (mTBI) generally reveal no overt structural brain lesion on routine magnetic resonance imaging (MRI) or computed tomography (CT) scans, microstructural and neurochemical changes have been proposed to account for slight but persistent deficits in this population. Kobori and Dash (2006) reported a general elevation of gamma aminobutyric acid (GABA) concentration hours after TBI in rats (Kobori and Dash, 2006 ). Transcranial magnetic stimulation (TMS) studies indicate increased GABAB receptor activity in patients after recurrent mTBIs (Tremblay et al., 2011 ). Our aim was to evaluate differences in cognition, GABA concentration and GABAB receptor activity between healthy controls and patients in the chronic phase after recurrent mTBIs. Methods: Seventeen subjects for the mTBI group (24.2 ± 2.8 years (mean + SD), 15.4 ± 2 years of education, 2 women) and 22 group-wise matched healthy controls without a history of mTBIs were included. Subjects of the mTBI group had to report sustaining at least 2 mTBIs at least 6 months prior to study enrollment (number of TBIs: 3.1 ± 1.6; last TBI in month: 21.2 ± 13.5). All participants received comprehensive cognitive testing and separate MRS and TMS sessions to determine GABA concentration and GABAB receptor activity, respectively. Results: The mTBI group performed trend-wise lower in most cognitive tests (Fig. 1 ). Student's t-tests revealed significant differences between groups in verbal fluency tasks, but no between-group differences in GABA concentration and GABAB receptor activity emerged. However, we found a significant positive correlation between number of mTBI and GABA concentration in mTBI patients (Fig. 2 ). Discussion: In line with recent reports, mTBI patients scored significantly lower in verbal fluency tasks (Tremblay et al., 2013 ). This slight deterioration of cognition may be due to subtle deficits in structural and functional connectivity after recurrent mTBI (List et al., 2015 ). Although we could not find differences in GABA concentration on a group-wise level, a significant correlation between the number of mTBI and GABA concentration may indicate a slight increase of GABA after recurrent mTBIs. Future studies should consider a prospective design from the acute over subacute into chronic phase after mTBI to determine the time-course of GABA alterations.